Hubungan Pengetahuan Ibu yang Memiliki Bayi Usia 0-12 Bulan dengan Pemberian Nasi Papah di Desa Semaya Kabupaten Lombok Timur - Jusmala Sari; Husniyati Sajalia; Ernawati; Siti Maesum (Universitas Muhammadiyah Klaten, 2022)
The tradition of nasi papah is rice that has been chewed and mashed before being given to babies, some even keep the rice papah to be given in the next few days. This tradition is an expression of affection between mother and baby, because of the contact of saliva between mother and child, which is believed to strengthen the relationship between mother and child, but without realizing it, this tradition has become a habit that has a negative impact on the health of the baby. This study aims to determine the relationship between knowledge of mothers who have babies aged 0-12 months with the provision of papah rice in Semaya Village, Sikur District, East Lombok Regency. This research is an analytic survey study with a cross sectional design, the number of research samples is 58 mothers who have babies aged 0-12 months with Accidental Sampling sampling technique. The results showed that most of the respondents were aged 20-35 years, namely 23 respondents (27.6%). Some of the high school education levels were 35 respondents (60.3%), and 45 (77.5%). Statistical test using Chi Square and obtained a significant value of 0.000 <0.05 which means that there is a relationship between the knowledge of mothers who have babies aged 0-12 months with the provision of papah rice. The conclusion of the study is that there is a relationship between the knowledge of mothers who have babies aged 0-12 months with the provision of papah rice.